Health impacts of prolonged unemployment and reemployment: A longitudinal study - Galić, Zvonimir; Šverko, Branimir; Maslić Seršić, Darja (2008)
In a three-way longitudinal survey of initially unemployed persons (N=370), we examined the impact of prolonged unemployment and reemployment on a series of self-assessed measures of both physical and mental health (captured by the SF-36 Health Survey). Already at T1, on most of the health indicators, the participants who remained unemployed scored lower then those who later gained employment. The participants reemployed at T2 and T3 exhibited improved health, but only on the mental-health indicators. The results suggest that poor physical health contributes to prolonged unemployment, while poor mental health both contributes to and results from unemployment.
29th International Congress of Psychology (20.-27.07.2008. ; Berlin, Njemačka)
Projekt MZOS
ENG